A case study of management characteristics and new product development. - Thoe, Choa Kheong. (2009)
This paper explores the changes in management characteristics as individual motivation and degree of complexity, uncertainty and ambiguity vary through stages in developing new products. Management characteristics are defined as autocratic, bureaucratic, entrepreneurial and team-based.